Influence of temperature on Ti:sapphire spectroscopic and laser characteristics. (7th June 2018) - Fibrich, M; Šulc, J; Jelínek, M; Jelínková, H; Kubeček, V
Abstract: We report on the influence of temperature on the spectroscopic and lasing properties of Ti:sapphire (Ti 3+  :Al2 O3 ) crystal. The fluorescence lifetime, polarization-resolved absorption and emission spectra, and laser characteristics at  ̃750 nm are described in detail within a temperature range of 78–300 K. The cooling of Ti:sapphire crystal down to cryogenic temperatures resulted in dramatic improvement in terms of its laser output power and oscillation threshold. More than two times better results were reached at 78 K when compared with room temperature operation. A continuous output power of 325 mW with a slope efficiency of 24% (related to absorbed pump power) was obtained using 98% output coupler reflectivity at a 750 nm wavelength at cryogenic temperatures. The corresponding oscillation threshold was 580 mW of absorbed pump power.